2021
DOI: 10.55601/jwem.v11i2.767
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Peranan Kepemimpinan Terhadap Kinerja Karyawan Secara Langsung dan Melalui Motivasi dan Kepuasan Kerja

Abstract: Secara teori, kepemimpinan merupakan salah satu faktor yang dapat mempengaruhi kinerja bawahan, namun pengaruh tersebut dapat secara tidak langsung atau melalui variabel intervening. Penelitian ini berusaha mencari bukti empiris dengan peran kepemimpinan bagi kinerja karyawan baik secara langsung maupun dimediasi oleh motivasi dan kepuasan kerja. Penelitian dilakukan pada PT. Jaya Anugrah Sukses Abadi dan pengumpulan data dilakukan dengan kuesioner terhadap 109 karyawan pada sebuah perusahaan, teknik sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…This means that leadership is capable of improving the performance of employees. These findings are also consistent with research conducted by [8], which also found similar results, where leadership has a positive impact on employee performance. This is also in line with social exchange theory, which explains that when employees are satisfied with the leadership style in a company and receive good treatment from a leader, they will respond by enhancing their performance.…”
Section: The Influence Of Leadership On Employee Performancesupporting
confidence: 92%
“…This means that leadership is capable of improving the performance of employees. These findings are also consistent with research conducted by [8], which also found similar results, where leadership has a positive impact on employee performance. This is also in line with social exchange theory, which explains that when employees are satisfied with the leadership style in a company and receive good treatment from a leader, they will respond by enhancing their performance.…”
Section: The Influence Of Leadership On Employee Performancesupporting
confidence: 92%
“…This is shown by the fact that most employees are happy to be given input by their superiors, one of which is through guidance so that it will stimulate work motivation and optimize performance. Study (Arifa & Muhsin, 2018;Syaifora, 2019;Ginting et al, 2021) The work environment does not affect employee performance because with the hybrid work system, employees are given the convenience of working from home and only going to the office when needed. Therefore, the office work environment does not directly affect employee performance.…”
Section: The Effect Of Leadership On Employee Performance Through Wor...mentioning
confidence: 99%